Virulence effect of Metarhizium anisopliae (Met.) and Beauveria bassiana (Bals.) fungi against the peach fruit fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae) - Ismail R. El-Gendy; Mohamed F. M. Zawrah; Mona I. El-Banobi (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background The peach fruit fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae), is a key pest of fruits in Egypt. Insect-pathogenic fungi are one of the biocontrol agents that increasingly substitute the traditional pesticides to overcome pesticide risks. Therefore, the present study aims to assess the fungal virulence of Beauveria bassiana (Balsamo) and Metarhizium anisopliae (Metchnikoff) against B. zonata pupae. Also, extended pathogenicity effect of these fungi on adult flies was studied. Results The results showed that M. anisopliae fungus had more pathogenicity to B. zonata pupae on the 2nd, 3rd, and 5th days post-treatment than B. bassiana. Pathogenicity fungal effects of treated larvae extended to the surviving adults. Fungal concentration and post-exposure interval reversely impacted the pupae by 63.88 and 63.59% mortality in the case of M. anisopliae and B. bassiana, respectively. The lethal concentration of treated fly by M. anisopliae (LC50 = 9.5 × 106 conidia/ml and LC90 = 9.9 × 107 conidia/ml) was lower than that of B. bassiana (LC50 = 5.1 × 107 conidia/ml and LC90 = 1.9 × 109 conidia/ml). Median lethal time (LT50) value was fungal species-dependent, and concentration. Metarhizium anisopliae was more virulent than B. bassiana; the lowest LT50 value was 9.48 days by M. anisopliae and 13.33 days by B. bassiana, depending on the fungal tested concentration of 2.3 × 106 conidia/ml. Conclusions The tested entomopathogenic fungi could be considered promising biocontrol agents against B. zonata and could be used for fly suppression through soil application in IPM programs.